Effects of Teriparatide versus Salmon Calcitonin Therapy for the Treatment of Osteoporosis in Asia: A Meta-analysis of Randomized Controlled Trials - Chen, Changjun; Alqwbani, Mohammed; Zhao, Jie; Yang, Ruitong; Wang, Songgang; Pan, Xin (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2021)
Objective: The objective of this meta-analysis was to compare the efficacy and safety of teriparatide versus salmon calcitonin for the treatment of osteoporosis in Asian patients and to investigate whether the results of global studies could be applicable to Asian patients. Methods: PubMed, OVID, Cochrane Central Register of Controlled Trials (CENTRAL) and EMBASE up to December 2018 were searched. Eligible randomized controlled trials (RCTs) that compared teriparatide versus salmon calcitonin in Asian osteoporosis population were included. Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines were used for data synthesis, and Cochrane Collaboration software Review Manager 5.3 was used to analyze the pooled data. Results: Three RCTs involving 529 patients were included (mean age 68.7 yr; 93.4% females; mean follow-up 6 months); outcome measures included bone mineral density (BMD) of the femoral neck, total hip and lumbar spine; bone markers and adverse events. We found that the period of 6-months of teriparatide treatment was helpful for the improvement of the BMD of lumbar vertebra, however, the improvement of BMD was not significant in the femoral neck and total hip joint. There was a positive correlation between bone-specific alkaline phosphatase (BSAP) and osteocalcin (OCN) and the response of Asian patients to subcutaneous injection of 20 micrograms per day of teriparatide. The proportion of the occurrence of adverse effects was more obvious in the teriparatide group compared with salmon calcitonin, but there was no significant difference. Conclusion: Results suggested that the use of teriparatide could improve the lumbar BMD by shortterm (six months) application in Asian osteoporosis patients, which is beneficial to the patients who cannot tolerate adverse events of long-term treatment. The BSAP and OCN bone markers could be useful to monitor the responses of Asian osteoporosis patients to teriparatide treatment. Finally, both of teriparatide and salmon calcitonin were well tolerated by Asian patients.
Keywords: Teriparatide